Signs and symptoms of genetic conditions : a handbook - Hudgins, Louanne; Toriello, Helga V.; Enns, Gregory M.; Hoyme, H. Eugene (Oxford University Press, 2014)
"Connecting an abnormal physical exam to the possible genetic condition is a daunting and inexact task for any physician, be they a primary care provider, non-geneticist specialist, or fellowship-trained geneticist. Comprising 31 clinical protocols from the world's foremost clinical geneticists, Signs and Symptoms of Genetic Conditions provides a practical manual for the diagnosis and management of common human genetic conditions based on their presenting signs and/or symptoms. Each chapter examines a specific clinical finding and leads the user through a step-by-step approach to a differential diagnosis."--Back cover